2017
DOI: 10.1002/etc.3898
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific metabolism of naphthalene and phenanthrene in 3 species of marine teleosts exposed to Deepwater Horizon crude oil

Abstract: The 2 most abundant polycyclic aromatic hydrocarbons (PAHs) measured in Deepwater Horizon crude oil, naphthalene and phenanthrene, and their associated homologs have both been shown to be acutely toxic in fish. Although fish have a relatively high metabolic capacity for PAHs, hydroxylated PAH (OH-PAH) derivatives formed during the initial metabolic response can negatively impact the health of fish. Species-specific metabolism of naphthalene and phenanthrene was evaluated in 3 marine teleosts, red drum (Scianop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 41 publications
2
6
0
1
Order By: Relevance
“…These structures were selected for broad coverage of environmental and metabolic byproduct prevalence. Hydroxy-PAHs were emphasized due to their ready formation as metabolites in fish and humans following PAH exposure, and by fossil fuel combustion and environmental oxidation (Diamanti-Kandarakis et al 2009; Luderer et al 2017; Pulster et al 2017; Simoneit et al 2007; Wang et al 2017). Furthermore, cytochrome P450, family 1, subfamily A (CYP1A) expression patterns were characterized for each compound as an indicator for AhR activation.…”
Section: Introductionmentioning
confidence: 99%
“…These structures were selected for broad coverage of environmental and metabolic byproduct prevalence. Hydroxy-PAHs were emphasized due to their ready formation as metabolites in fish and humans following PAH exposure, and by fossil fuel combustion and environmental oxidation (Diamanti-Kandarakis et al 2009; Luderer et al 2017; Pulster et al 2017; Simoneit et al 2007; Wang et al 2017). Furthermore, cytochrome P450, family 1, subfamily A (CYP1A) expression patterns were characterized for each compound as an indicator for AhR activation.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, M. bahia and M. chulae mortality increased in 1.25% wash water, with close to all M. bahia being dead at 10% wash water and the mortality rate of M. chulae in 20% wash water was only 42.5% in our study. The discrepancy can be explained either by the difference in the chemical compositions of wash water from these three studies or by the difference in sensitivity of the test organisms -sh has a relatively high metabolic capacity for PAHs [50] , therefore, compared to copepods or mysid, sh might be decreased potential susceptibility to adverse effects to wash water. Hunt et al [51] observed marine mysid (Mysidopsis intii) was more sensitive to Ni than the marine sh (Atherinops a nis).…”
Section: Mortalitymentioning
confidence: 93%
“…In multispecies exposure trials conducted at the Mote Marine Laboratory post-DWH, Pulster et al (2017) exposed red drum, Florida pompano (Trachinotus carolinus), and southern flounder to intraperitoneal injections of DWH crude. Although fishes have a high capacity for metabolizing PAHs, their ability to metabolize subsequent metabolites is poorly understood.…”
Section: Evolving Perspectives From Dwh-related Research On the Measurement And Assessment Of Ecotoxicological Effectsmentioning
confidence: 99%